Needs of ethnic minority students for learning improvement in secondary schools - Kabir, Md. Mahbubul; Nath, Samir Ranjan (BRAC Research and Evaluation Division (RED), 2019)
This study aimed to investigate the needs of ethnic minority students for learning improvement in secondary schools through an in-depth understanding of the factors affecting their poor performance. Findings reconfirmed the poor performance of ethnic minority students. An analysis of influential factors within and outside of school indicated that a weak foundation in Bangla language along with continuous economic crises, teachers' inefficient teaching methods and irregular attendance, parental disinterest, other responsibilities outside school, weak educational foundation in primary school stimulated and perpetuated a sub-standard performance in general. Support systems in place seemed to upgrade a few good platforms at the same time neglecting the vast majority of pupils. This study revealed prime needs of ethnic minority students for learning improvement to be: developing a good foundation in Bangla as a second language; raising the quality of classroom teaching and need-based curriculum reinforcement for slow learners; sensitising teachers to issues specific to ethnic pupils; eradicating irregularities in the testing system; creating a space to facilitate increased interaction between ethnic and Bangali pupils; and developing a comprehensive support system for general and slow learners.